1990
DOI: 10.1002/jsfa.2740530112
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid composition of pea (Pisum sativum) proteins and protein profile of pea flour

Abstract: The influence of coarse milling on the distribution of the protein jiactions in the particles was studied. The profile in proteins was the same for the diferent classes as that for the whole seed. The second part of the work was devoted to the determination of the amino acid composition of the different nitrogenous jiactions.Pea seeds (Pisum sativum L) are mostly used in pig feed because of their low content of antinutritional factors and their high nutritive value. Pea proteins are, however, deficient in Scon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 7 publications
4
29
0
Order By: Relevance
“…At a lower scale, the protein network in cooked pasta was weaker in legume pasta compared with durum wheat pasta: cooked legume pasta and especially faba bean pasta presented a higher proportion of proteins linked by non-covalent interactions and a lower proportion of proteins linked by disulphide and other covalent bonds. Legume proteins, mainly composed of globulins and albumins [25][26][27][28][29] , are poor in sulphur-containing amino acids, especially cystein residues. 2,3 The lack of sulphur groups could explain the lower potential of legume proteins to bind through disulphide bonds compared with gluten proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At a lower scale, the protein network in cooked pasta was weaker in legume pasta compared with durum wheat pasta: cooked legume pasta and especially faba bean pasta presented a higher proportion of proteins linked by non-covalent interactions and a lower proportion of proteins linked by disulphide and other covalent bonds. Legume proteins, mainly composed of globulins and albumins [25][26][27][28][29] , are poor in sulphur-containing amino acids, especially cystein residues. 2,3 The lack of sulphur groups could explain the lower potential of legume proteins to bind through disulphide bonds compared with gluten proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Globulins and albumins represented 45-60% and 14-30% of split pea proteins; 55-75% and 2-33% of faba bean proteins respectively. [25][26][27][28][29] Durum wheat semolina proteins were characterised by a low solubility in water (11.1%; Table 1). In comparison, legume flour proteins were highly soluble, especially faba bean flour (78.8%) which is in accordance with previous study.…”
Section: Chemical Composition Solubility In Water and Heat Sensitivimentioning
confidence: 99%
“…O'Kane et al (2004) found legumin: vicilin ratios varying from 0.2 to 1.5. Compared to the globulins, pea albumins contain more of the essential amino acids tryptophan, lysine, threonine, cysteine and methio- (Leterme, Monmart, & Baudart, 1990). B Unit: g/100 g protein (Khattab, Arntfield, & Nyachoti, 2009).…”
Section: Peamentioning
confidence: 98%
“…Thus, our strategy to follow the intramolecular crosslinks is based on size measuring methods by using SDS-PAGE and DLS techniques. To validate our hypothesis, we first selected the pea albumin protein fraction as substrate to MTGase because pea albumin (i) is easy to extract and to purify, (ii) is rich in glutamine and lysine (Bhatty, 1982;Leterme, Monmart, & Baudart, 1990), and (iii) is a small protein composed of an abundant polypeptide (PA2 = 26 kDa) which can be easily followed by SDS-PAGE. Next, TPA was treated at decreasing protein concentration (down to 0.01% w/w) with MTGase in order to promote intramolecular crosslinks.…”
Section: Resultsmentioning
confidence: 99%